2015
DOI: 10.1053/j.sodo.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic loading (vibration) accelerates tooth movement in orthodontic patients: A double-blind, randomized controlled trial

Abstract: Keywords -Accelerated orthodontic tooth movement; Effect of vibrations on tooth movement; Effect of vibrations on bone; Cyclic loading and tooth movement; AcceleDent and tooth movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 33 publications
(27 reference statements)
2
115
1
8
Order By: Relevance
“…31 There is currently data from retrospective studies and two randomized clinical trials showing evidence of increased rates of tooth movement and reduced pain when using fixed appliances combined with supplemental vibrational force. [32][33][34] However, retrospective studies are known to be associated with bias and an exaggeration of treatment effects, 35 whilst both the existing randomized trials are at risk of bias. 36 Indeed, advertisement claims and the promising results of the early pilot studies have not been confirmed by subsequent well-designed randomized clinical trials that have shown no improvement in either tooth alignment rates or pain experience associated with supplemental vibrational force.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…31 There is currently data from retrospective studies and two randomized clinical trials showing evidence of increased rates of tooth movement and reduced pain when using fixed appliances combined with supplemental vibrational force. [32][33][34] However, retrospective studies are known to be associated with bias and an exaggeration of treatment effects, 35 whilst both the existing randomized trials are at risk of bias. 36 Indeed, advertisement claims and the promising results of the early pilot studies have not been confirmed by subsequent well-designed randomized clinical trials that have shown no improvement in either tooth alignment rates or pain experience associated with supplemental vibrational force.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Similarly, Woodhouse et al found no evidence that supplemental vibrational force can increase the rate of initial tooth movement or reduce the amount of time required to achieve final alignment when used in conjunction with a preadjusted conventional appliance (15). Contrary to these findings, Pavlin et al (19) reported that low-level cycling loading of 0.25N at 30 Hz released by the same vibrational appliance used in the study of Miles et al increases the rate of orthodontic tooth movement (OTM) when applied as adjunct to orthodontic treatment. In a recent study Leethankul et al investigated through a split-mouth study the levels of IL-1β in gingival cervicular fluid and the rate of orthodontic tooth movement in canines stimulated by electric toothbrush compared to standard orthodontic movement of canines (16).…”
Section: Ivyspring International Publishermentioning
confidence: 46%
“…Dubravko et al used the AcceleDent device (OrthoAccel Technologies, Inc., Bellaire, USA) to generate a vibration of 0.25 N and a frequency of 30 Hz. 54 It was possible to accelerate the distalization of canines with skeletal anchorage by 48.1% compared to the control group (1.16 mm vs 0.79 mm/month). Other reports have also confirmed the accelerating effect of vibrations.…”
Section: Vibrationsmentioning
confidence: 96%